Adoption of Digital Leadership Style in Guiding Deviant Behavior of Police Personnel at Metro Jaya Regional Police - Hayati, Valent Furi; S., Basir; Gani, Yopik (International Journal of Social Science and Community Service, 2025)
Digital leadership style emphasizes the leader's ability to understand information technology and digital systems, data-driven decision making and analysis, quick response to environmental and technological changes, emphasis on information transparency, innovation, creative thinking, and inspiring change. This scientific article aims to conceptualize the adoption of digital leadership in coaching against misconduct of Polri members at Metro Jaya Regional Police. The method used is a qualitative approach with descriptive analytics to provide detailed descriptions of occurring situations. The data used includes primary and secondary data. Data collection techniques include observation, interviews, and document studies. The author tests data accuracy and validity using triangulation techniques. Research results show that leadership at Metro Jaya Regional Police still faces several weaknesses such as being militaristic in nature, lacking measurable future digital vision, limited managerial capabilities, insight and understanding of technology-based transparency concepts, limited mastery of digital-based facilities and infrastructure, minimal problem-solving policing capabilities, and insufficient attention to digital development and environmental directions. Strategies that can be applied in implementing digital leadership in coaching against misconduct of Polri members at Metro Jaya Regional Police include establishing vision, mission, and strategic direction of digitalization in member coaching, building digital systems that support coaching and early detection of violations, improving personnel capabilities in using and managing digital systems, operating digital systems gradually and integrated into coaching processes, assessing implementation effectiveness and conducting continuous improvement, and making digital leadership an embedded work culture.